Occurrence of Helminthostachys zeylanica Hook. In Lakshmipur Forest (Gorakhpur) - Dixit, S. N.; Tripathi, S. M. (Indian Forester, 1966)
Helminthostachys Zeylanica Hook. Which is recorded by Beddome (1883) from Western parts of South India, Assam and Bengal has now been observed in Lakshmipur Forest (Gorakhpur). Roy and Kumar (19591 reported its Occurrence in Kusmi Forest in association with Eugenia heyneana. Due to deforestation of Eugenia trees the fern is fast disappearing. In Lakshmipur Forest, however, a very rich and luxuriant growth or Helminthostachys has heen observed. It is suggested that the Forest authorities must take proper care to avoid any damage to this rare fern and declare this as restricted plant.